Sketch Learning by Using Demonstration Method for Early Semester Students - Muslim Muslim (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This study is purposed to describe sketch learning by using demonstration method for early semester students in which the sketch learning by using demonstration method is a good way to develop the creativity of early students because not all of them have the ability to make sketches. This study used a CAR (Classroom Action Research) research method in which 36 art students were the subjects of this study. The study results explained that in cycle I of CAR, the ability of the students in sketch learning was still low because out of 36 students, there were 25 students (69.4%) who received a pretty good predicate and 11 students (30.6%) who got a good predicate, so it needs the cycle II of CAR. In the cycle II of CAR, the results obtained were very satisfying where out of 36 students there were 7 students (19.4%) who received a pretty good predicate, 28 students (77.8%) who got a good predicate and only 1 student (2.8 %) got a very good predicate. Therefore, learning sketches using the demonstration method is a good way to apply to early semester students in developing the students' skills in learning sketches.